Associations between maternal depressive symptoms and risk for offspring early-life psychopathology: the role of genetic and non-genetic mechanisms. Issue 3 (9th February 2021) - Gjerde, Line C.; Eilertsen, Espen M.; Hannigan, Laurie J.; Eley, Thalia; Røysamb, Espen; Reichborn-Kjennerud, Ted; Rijsdijk, Fruhling V.; McAdams, Tom A.; Ystrom, Eivind
Abstract: Background: Although maternal depressive symptoms are robustly associated with offspring early-life psychopathology symptoms, it is not clear which potential mechanisms are at play. We aimed to estimate the relative importance of genetic transmission and direct environmental exposure in these associations on three occasions in early childhood. Methods: Biometric modeling of maternal sisters and their offspring from the Norwegian Mother and Child Cohort Study. The analyzed sample comprised 22 316 mothers and 35 589 offspring. Mothers reported their own depressive symptoms using the Symptom checklist, and offspring's concurrent symptoms of psychopathology using the Child Behavior Checklist at 1.5, 3, and 5 years postpartum. Results: Associations between maternal symptoms of depression and offspring emotional problems were predominantly explained by passive genetic transmission at 1.5 and 3 years postpartum. At age 5, associations were more due to direct environmental exposure. For offspring behavioral problems, there was no net increase in the importance of direct environmental exposure across occasions. Conclusions: Associations between maternal depressive symptoms and offspring psychopathology symptoms remained after accounting for shared genes, consistent with a small, causal effect. For offspring emotional problems, this effect appeared to increase in importance over time. Our findings imply that treatment of maternal depressive symptoms could also benefit the offspring, and that genetic confounding should be considered in future studies of such mother–offspring associations.